EFEKTIVITAS PEMANFAATAN RUANG DI DISTRIK FEF KABUPATEN TAMBRAUW (The Effectiveness of Space Use in Fef District, Tambrauw Rengency) - Airo Gussteva Hetharia; Paulus A. Pangemanan; Leonardus R. Rengkung (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2023)
This study aims to determine the effectiveness of space utilization in the Fef District, Tambrauw Regency. This research was conducted from June 2022 to July 2022. The data used in this research is primary data obtained from in-depth interviews. Methods of data analysis using Qualitative Analysis which consists of Data Reduction, Data Presentation and Drawing Conclusions. The results of the study show that the use of space is not effective, this is due to several things, especially in the internal handling of the organization, which, among other things, when viewed from the ability of human resources, it turns out that there is less response. Factors that influence the effectiveness of space utilization is the ability of employees. The smooth performance of BAPPEDA in carrying out effective use of space in the Fef District is largely determined by the ability of existing staff, because Bapedda employees, especially those in charge of carrying out planning, are the spearhead of the organization's wheels. Therefore it is necessary to get attention in handling it in addition to other factors of course.